Polymer electrolyte hybrid dielectric film material based on inorganic chloride doping as well as preparation method and application of polymer electrolyte hybrid dielectric film material

By using inorganic chloride-doped polymer electrolyte hybrid dielectric thin film materials in organic transistors, the problem that organic transistor memory in the prior art is difficult to achieve multi-stage storage characteristics, and high-performance storage functions at low voltages are realized and fast storage operations.

CN119307142AActive Publication Date: 2025-01-14CHONGQING UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411385175.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-14
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

It is difficult for existing organic transistor memories to achieve multi-stage storage characteristics while having both flexibility and low operating voltage, and the ferroelectric characteristics are susceptible to external interference to affect storage performance, limiting their application.

Method used

Using polymer electrolyte hybrid dielectric film materials based on inorganic chloride doping, the polymer electrolyte is prepared by adding 0.05-20 wt.% inorganic chloride, such as zinc chloride, calcium chloride, copper chloride, etc. to the polymer electrolyte. A dielectric thin film with improved ion migration capability is produced and used in organic transistors to realize a dual-layer dielectric layer structure.

Benefits of technology

It realizes the effective regulation of the storage properties of organic transistors at low voltages, significantly reduces the threshold voltage, enhances ion conduction capabilities, supports multi-stage storage characteristics and fast storage operations, and is suitable for flexible low-power electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307142A_ABST
    Figure CN119307142A_ABST
Patent Text Reader

Abstract

The invention relates to a polymer electrolyte hybrid dielectric film material based on inorganic chloride doping and a preparation method and application thereof, and belongs to the technical field of dielectric film materials and devices. The polymer electrolyte hybrid dielectric film material based on inorganic chloride doping has significantly enhanced capacitance and ion migration capability, and can be used for developing an organic transistor memory with multi-level response to different pulse voltages, and the device can realize a wide memory window of 0.548 V under a low working voltage of-1.5 V. The memory also shows good static and dynamic storage characteristics, and accurate regulation and identification of memory windows with different sizes can be realized by programming grid pulse voltage. The novel polymer electrolyte hybrid dielectric film material and the organic transistor memory with the multilevel storage characteristic have the advantages of simple structure, excellent performance, easiness in large-scale manufacturing and the like, and have good popularization and application prospects in the technical fields of low-power consumption optoelectronic devices and storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of dielectric film materials and devices, and relates to a polymer electrolyte hybrid dielectric film material based on inorganic chloride doping, and a preparation method and application thereof. Background Art

[0002] The continuous development of the Internet of Things and artificial intelligence technologies has led to an explosive growth in the amount of data, so there is an urgent need to develop high-performance advanced storage materials and devices. Memory is a component used in digital communications, computer equipment and electronic instruments to temporarily or long-term store program running data and instructions so that data can be accessed and processed at any time. Organic field-effect transistors (OFETs) can achieve synaptic plasticity, data storage, and in-memory computing due to the easy-to-regulate properties of key components such as organic semiconductors and gate dielectric layers. They have gradually developed into a new generation of storage devices and have broad application prospects in the field of advanced storage technology.

[0003] Recently, the research on organic transistor memory devices has mainly focused on the selection of dielectric layer materials and the design of floating gate device structures. Compared with floating gate device structures, organic transistor memories based on functional dielectric layer materials are gaining increasing attention because of their diverse material selections and the ability to control the structure and properties of materials in multiple ways to adjust the changes in device parameters to achieve storage characteristics. Despite this, most current research on organic transistor memories focuses on widening the memory window, and few studies have been conducted on organic transistor memory devices that can achieve multi-level storage characteristics while being flexible and having low operating voltage. In response to the needs of wearable applications and other fields, it is important to develop flexible, low-voltage organic transistor memories that can meet multi-level storage characteristics. At present, a common method is to prepare functional materials with charge transfer characteristics as the dielectric layer of organic transistor memories, and to achieve storage functions by precisely regulating device performance, but this method is difficult to reduce the operating voltage of the device. In addition, the use of dielectric layer materials with ferroelectric polarization characteristics can also achieve the storage function of organic transistors, but the ferroelectric properties in organic material systems are easily affected by external interference and affect storage performance, thereby limiting the application of organic transistor memories.

[0004] Polymer electrolyte material systems can utilize the ion migration ability in the electrolyte to change the capacitance and dielectric constant of the dielectric layer, and are expected to realize the storage function of organic transistor memory. However, it is still extremely challenging to simultaneously realize flexible low-voltage operation and multi-level storage characteristics of organic transistor memory. Therefore, it is necessary to develop a new polymer electrolyte hybrid dielectric material system based on inorganic chloride-doped polymer electrolytes, which is of great significance for the design and optimization of high-performance organic transistor memory. Summary of the invention

[0005] In view of this, one of the objects of the present invention is to provide a polymer electrolyte hybrid dielectric thin film material based on inorganic chloride doping; the second object of the present invention is to provide a method for preparing a polymer electrolyte hybrid dielectric thin film material based on inorganic chloride doping; the third object of the present invention is to provide an application of a polymer electrolyte hybrid dielectric thin film material based on inorganic chloride doping in the preparation of an organic transistor memory, optoelectronic devices or electrical equipment; the fourth object of the present invention is to provide an organic transistor memory; the fifth object of the present invention is to provide a method for preparing an organic transistor memory; the sixth object of the present invention is to provide an application of an organic transistor memory in static storage and dynamic storage and optoelectronic devices or electrical equipment.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] 1. According to one aspect of the present invention, there is provided a polymer electrolyte hybrid dielectric film material based on inorganic chloride doping, wherein the polymer electrolyte hybrid dielectric film material comprises a polymer electrolyte material and a doped inorganic chloride, wherein the mass of the inorganic chloride accounts for 0.05 to 20 wt.% of the total mass of the inorganic chloride and the polymer electrolyte material;

[0008] The polymer electrolyte material is at least one of acrylamide polymer electrolytes or their derivatives, acrylic acid polymer electrolytes or their derivatives, acrylic acid polymer electrolytes or their derivatives, polymer electrolyte composite dielectric materials formed by blending polyacrylic acid and polyethylene glycol, and polymer electrolyte composite dielectric materials formed by blending polyacrylic acid and polyvinyl alcohol.

[0009] Preferably, the inorganic chloride is any one or more of zinc chloride, calcium chloride, ferric chloride, copper chloride, cobalt chloride, magnesium chloride, lithium chloride, sodium chloride or potassium chloride.

[0010] Preferably, the mass ratio of polyacrylic acid to polyethylene glycol in the polymer electrolyte composite dielectric material formed by blending polyacrylic acid and polyethylene glycol is 1:0.1 to 1:0.6, and the mass ratio of polyacrylic acid to polyvinyl alcohol in the polymer electrolyte composite dielectric material formed by blending polyacrylic acid and polyvinyl alcohol is 1:0.1 to 1:0.7.

[0011] 2. According to another aspect of the present invention, a method for preparing the above-mentioned inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material is provided, the preparation method comprising the following steps:

[0012] (1) dissolving a polymer electrolyte in a solvent and stirring at room temperature to obtain a precursor solution of the polymer electrolyte;

[0013] (2) adding an inorganic chloride to a precursor solution of the polymer electrolyte, and stirring the mixture at room temperature to obtain an inorganic chloride-doped polymer electrolyte solution;

[0014] (3) After the inorganic chloride-doped polymer electrolyte solution is spin-coated to form a film, the film is annealed at 50-200° C. for more than 30 minutes to obtain an inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material.

[0015] Preferably, in step (1), the solvent is any one or more of water, methanol, ethanol or isopropanol, and the concentration of the polymer electrolyte in the polymer electrolyte precursor solution is 3 to 60 mg / mL;

[0016] In step (2), the stirring time at room temperature is 3 to 24 hours.

[0017] Further preferably, in step (1), the solvent is any one of methanol, ethanol or isopropanol, and the concentration of the polymer electrolyte in the polymer electrolyte precursor solution is 10 to 50 mg / mL;

[0018] More preferably, in step (1), the solvent is methanol or ethanol, and the concentration of the polymer electrolyte in the polymer electrolyte precursor solution is 15 to 45 mg / mL.

[0019] 3. According to another aspect of the present invention, there is provided an application of the above-mentioned inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material in the preparation of organic transistor memory, optoelectronic devices or electrical equipment.

[0020] 4. According to another aspect of the present invention, an organic transistor memory is provided, which comprises, from bottom to top, a substrate, a semiconductor layer, a double dielectric layer formed by an interface passivation dielectric layer and a polymer electrolyte hybrid dielectric layer, and a gate, and a source electrode and a drain electrode are respectively arranged between the surface of the substrate and the semiconductor layer;

[0021] The material of the polymer electrolyte hybrid dielectric layer comprises the above-mentioned inorganic chloride-doped polymer electrolyte hybrid dielectric film material.

[0022] 5. According to another aspect of the present invention, a method for preparing the above-mentioned organic transistor memory is provided, the method comprising the following steps:

[0023] (1) preparing a source electrode material and a drain electrode material on a substrate surface by any one of magnetron sputtering, vacuum thermal evaporation, atomic layer deposition, inkjet printing or drop coating to form a source electrode and a drain electrode, wherein a conductive channel with a micro-nano scale spacing is formed between the source electrode and the drain electrode;

[0024] (2) preparing an organic semiconductor material on the surface of the source electrode, the drain electrode and the substrate to form a semiconductor layer by any one of spin coating, blade coating or inkjet printing;

[0025] (3) on the surface of the semiconductor layer, the material of the interface passivation dielectric layer is prepared by any one of atomic layer deposition, vacuum thermal evaporation, magnetron sputtering, spin coating, blade coating or inkjet printing to form an interface passivation dielectric layer;

[0026] (4) coating the inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material on the surface of the interface passivation dielectric layer by any one of the solution processing methods of spin coating, blade coating or inkjet printing, and then annealing to prepare an inorganic chloride-doped polymer electrolyte hybrid dielectric layer;

[0027] (5) On the surface of the inorganic chloride-doped polymer electrolyte hybrid dielectric layer, a gate material is prepared by any one of magnetron sputtering, vacuum thermal evaporation, atomic layer deposition, inkjet printing or drop coating to form a gate, thereby obtaining an organic transistor memory.

[0028] Preferably, in step (1), the material of the substrate is any one or more of polyethylene terephthalate, polyethylene naphthalate, polyimide, polydimethylsiloxane, polycarbonate, polyvinyl alcohol, glass, silicon dioxide / silicon or sapphire, and the source and drain materials are any one or more of gold, silver, aluminum, copper, chromium, platinum, titanium, nickel, indium tin oxide, fluorine-doped tin oxide, zinc aluminum oxide, carbon nanotubes, graphene or conductive polymers;

[0029] In step (2), the material of the semiconductor layer is an organic conjugated polymer or an organic small molecule semiconductor material, and the material of the semiconductor layer includes any one or more of poly (3-hexylthiophene), indacen-dithiophene-benzothiadiazole copolymer, polythiophene derivatives, polyfluorene derivatives, poly(p-phenylene vinylene) derivatives, pentacene, 7,7,8,8-tetracyanoquinodimethane or copper phthalocyanine;

[0030] In step (3), the material of the interface passivation dielectric layer is any one or more of polymethyl methacrylate, polystyrene, a polymer with a dielectric constant greater than 3, a metal oxide dielectric or silicon dioxide;

[0031] In step (4), when spin coating is used as the solution processing method, the spin coating speed is 200 to 5000 rpm, the spin coating time is 20 to 150 s, the temperature of the annealing treatment after spin coating is 50 to 200° C., and the annealing time is not less than 30 min;

[0032] In step (5), the gate material is any one or more of gold, silver, aluminum, copper, chromium, platinum, titanium, nickel, indium tin oxide, fluorine-doped tin oxide, zinc aluminum oxide, carbon nanotubes, graphene or conductive polymers.

[0033] Further preferably, in step (1), the material of the substrate is any one or more of polyethylene naphthalate, polyethylene terephthalate, polyimide or polydimethylsiloxane, and the material of the source and drain is any one of gold, silver, aluminum or copper;

[0034] In step (2), the material of the semiconductor layer is an organic conjugated polymer material, and the material of the semiconductor layer includes any one or more of poly (3-hexylphene), indacen-dithiophene-benzothiadiazole copolymer, polyfluorene derivative, and poly (p-phenylene vinylene) derivative;

[0035] In step (3), the material of the interface passivation dielectric layer is any one or more of polymethyl methacrylate or polystyrene;

[0036] In step (4), when spin coating is used as the solution processing method, the temperature of the annealing treatment after spin coating is 80 to 150° C.;

[0037] In step (5), the gate material is any one of gold, silver, aluminum or copper.

[0038] 6. According to another aspect of the present invention, there is provided application of the organic transistor memory in static storage, dynamic storage, optoelectronic devices or electrical equipment.

[0039] The beneficial effects of the present invention are:

[0040] 1. The present invention discloses a polymer electrolyte hybrid dielectric film material based on inorganic chloride doping, which mainly includes a polymer electrolyte material and a doped inorganic chloride, and has the following advantages: (1) It can realize the regulation of ion migration under an applied voltage to change the capacitance of the polymer electrolyte hybrid dielectric film, which not only successfully realizes the improvement and tuning of capacitance, but also can be used to conveniently adjust the storage properties of organic transistors; in addition, different inorganic chlorides are doped into the polymer electrolyte dielectric film, which will significantly increase the number of free ions in the film, improve the ion conduction ability of the film, and affect the electrical properties of the film, providing an effective way to regulate and optimize the electrical properties of the polymer electrolyte dielectric film material and its organic transistor. (2) This type of material is rich in source, low in cost, insensitive to thickness, and easy to process on a large scale and manufacture on a large scale, and has unique advantages in constructing high-performance, flexible, low-power organic transistors and their memories. (3) By utilizing the inorganic chloride doping effect of this type of dielectric film material, the ion migration ability and double layer effect within the polymer electrolyte dielectric film material can be greatly enhanced, so that organic transistors and their memories can work more efficiently under low voltage conditions, and the threshold voltage is also greatly reduced, which is conducive to the design and development of low-power electronic devices.

[0041] 2. The present invention also discloses an organic transistor memory, which uses an inorganic chloride-doped polymer electrolyte hybrid dielectric film material as the component material of the double-layer dielectric layer, and can achieve excellent static storage and dynamic storage characteristics. Under the influence of the programming gate pulse voltage, the ions in the inorganic chloride-doped polymer electrolyte hybrid dielectric film will migrate to different positions of the film, which can realize the multi-level storage characteristics of the organic transistor memory; and the memory can be effectively written by the programming gate pulse voltage, and can be erased by the reverse programming gate pulse voltage and ultraviolet light irradiation, and can realize the rapid writing of electric pulses to meet the application requirements of convenient storage. These technologies break through the limitations of the traditional strategy of organic transistor memory using a floating gate device structure to realize storage functions, and provide new options and beneficial ideas for the construction of high-performance organic transistor memory.

[0042] Other advantages, objectives and features of the present invention will be described in the following description to some extent, and to some extent, will be obvious to those skilled in the art based on the following examination and study, or can be taught from the practice of the present invention. The objectives and other advantages of the present invention can be realized and obtained through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:

[0044] Figure 1 This is a schematic diagram of the structure of an organic transistor memory based on zinc chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 4;

[0045] Figure 2 This is the EDS element distribution diagram of the hybrid dielectric thin film material based on zinc chloride doped polymer electrolyte prepared in Example 1 at the initial stage and after voltage application;

[0046] Figure 3 The transfer (a) and output (b) characteristic curves of the organic transistor memory based on the zinc chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 4;

[0047] Figure 4 The multi-level writing characteristics of the organic transistor memory based on the zinc chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 4, wherein the gate pulse voltage action time in a, b and c is 2s, 10s and 30s respectively;

[0048] Figure 5 The erase characteristics of the organic transistor memory based on the zinc chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 4;

[0049] Figure 6 The positive bias (a) and negative bias (b) electrical pulse response characteristics of the organic transistor memory based on the zinc chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 4;

[0050] Figure 7 The positive bias (a) and negative bias (b) electrical pulse response characteristics of the organic transistor memory based on the copper chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 5;

[0051] Figure 8 The positive bias (a) and negative bias (b) electrical pulse response characteristics of the organic transistor memory based on the ferric chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 6;

[0052] Among them, in the structural diagram of the organic transistor memory, 1 is the substrate, 2 is the source, 3 is the drain, 4 is the semiconductor layer, 5 is the interface passivation dielectric layer, 6 is the inorganic chloride-doped polymer electrolyte hybrid dielectric layer, and 7 is the gate. DETAILED DESCRIPTION

[0053] The following describes the embodiments of the present invention by specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments only illustrate the basic concept of the present invention in a schematic manner, and the following embodiments and features in the embodiments can be combined with each other without conflict.

[0054] The inorganic chloride-doped polymer electrolyte films used in the following examples use organic polymer electrolyte materials (PAA and PEG);

[0055] The structural formula of PAA and PEG is Where n is a positive integer.

[0056] The inorganic chlorides used for doping are zinc chloride, calcium chloride, copper chloride and ferric chloride.

[0057] If no specific conditions are specified in the following examples, the reactions were carried out under conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials and solvents in the examples of the present invention were purchased from commercial sources, including:

[0058] Organic polymer semiconductor material indomethacrylic acid-benzothiadiazole copolymer was purchased from Shenzhen Ruixun Optoelectronic Material Technology Co., Ltd.;

[0059] Chlorobenzene solvent and methanol solvent were purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;

[0060] Polyacrylic acid and polyethylene glycol were purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;

[0061] Zinc chloride, calcium chloride, copper chloride, and ferric chloride were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0062] Polystyrene was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;

[0063] Butyl acetate solvent was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0064] Example 1

[0065] A zinc chloride-doped polymer electrolyte hybrid dielectric thin film material is prepared by a solution spin coating method, and the specific method is as follows:

[0066] (1) dissolving polyacrylic acid and polyethylene glycol in a mass ratio of 7:3 in methanol to obtain a polymer electrolyte precursor solution, so that the concentration of polyacrylic acid in the polymer electrolyte precursor solution is 30 mg / mL, adding zinc chloride to the polymer electrolyte precursor solution (the mass fraction of the added zinc chloride in the whole solute (polyacrylic acid, polyethylene glycol and zinc chloride) is 2.62 wt.%), stirring at room temperature for 5 h to make the mixture uniformly mixed, and obtaining a zinc chloride-doped polymer electrolyte solution;

[0067] (2) In a glove box with a nitrogen atmosphere, spin-coat a 5 mg / mL interface passivation dielectric layer solution (dissolve 5 mg of polystyrene in 1 mL of butyl acetate and stir at room temperature for 5 h to obtain an interface passivation dielectric layer solution) onto a polyethylene naphthalate substrate (the spin coating process has a rotation speed of 2000 rpm and a spin coating time of 30 s) to form an interface passivation dielectric layer, and then spin-coat the zinc chloride-doped polymer electrolyte solution prepared in step (1) onto the interface passivation dielectric layer film (the spin coating process has a rotation speed of 500 rpm, a spin coating time of 30 s, and the spin coating is repeated twice), and annealing is performed on a heating table at 80° C. for 20 min to obtain a zinc chloride-doped polymer electrolyte hybrid dielectric film material.

[0068] Example 2

[0069] A copper chloride-doped polymer electrolyte hybrid dielectric film material, the preparation method of which is specifically as follows:

[0070] The "zinc chloride" in Example 1 is changed to "copper chloride", and the rest is the same as Example 1.

[0071] Example 3

[0072] A calcium chloride-doped polymer electrolyte hybrid dielectric film material, the preparation method of which is specifically as follows:

[0073] The "zinc chloride" in Example 1 is changed to "calcium chloride", and the rest is the same as Example 1.

[0074] Example 4

[0075] An organic transistor memory, the structural schematic diagram of which is as follows Figure 1 As shown, it includes the following structures from bottom to top: substrate 1, semiconductor layer 4, double dielectric layer (wherein the interface passivation dielectric layer 5 is located on the semiconductor layer 4, and the inorganic chloride-doped polymer electrolyte hybrid dielectric layer 6 is located on the interface passivation dielectric layer 5), gate 7, and the source 2 and drain 3 having channel patterns are respectively located on the surfaces of both ends of the substrate 1. The preparation method of the organic transistor memory based on the inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material is as follows:

[0076] (1) Using 125 μm thick polyethylene naphthalate as the substrate;

[0077] (2) On the surfaces of both ends of the substrate, gold was deposited through a mask using a vacuum thermal evaporation process (vacuum degree of about 2×10 -4 Pa, evaporation rate is about ) preparing a 50 nm thick source electrode and a drain electrode, respectively, wherein there is a channel with a width and a length of 22.5 mm and 0.15 mm respectively between the prepared source electrode and the drain electrode, to obtain a substrate having a source electrode and a drain electrode;

[0078] (3) In a glove box with a nitrogen atmosphere, a chlorobenzene solution of indole-1-dithiophene-benzothiadiazole copolymer with a concentration of 5 mg / mL was prepared and spin-coated onto the substrate having a source electrode and a drain electrode obtained in step (2) (wherein the rotation speed during the spin coating process was 2000 rpm and the spin coating time was 30 s). After the spin coating was completed, the semiconductor layer was prepared by annealing on a heating table at 90° C. for 20 min;

[0079] (4) In a glove box with a nitrogen atmosphere, a 5 mg / mL polystyrene butyl acetate solution was spin-coated onto the semiconductor layer obtained in step (3) (wherein the spin-coating speed was 2000 rpm and the spin-coating time was 30 s), and then allowed to stand for 10 min to form an interface passivation dielectric layer;

[0080] (5) In a glove box with a nitrogen atmosphere, the solution of the zinc chloride-doped polyelectrolyte hybrid dielectric film material prepared in Example 1 was spin-coated onto the interface passivation dielectric layer obtained in step (4) (wherein the spin-coating speed was 500 rpm, the spin-coating time was 30 s, and the number of spin-coatings was twice), and then annealed on a heating table at 90° C. for 120 min to prepare an inorganic chloride-doped polymer electrolyte hybrid dielectric layer;

[0081] (6) On the above inorganic chloride-doped polymer electrolyte hybrid dielectric layer, a vacuum thermal evaporation process (vacuum degree of about 2×10 -4 Pa, evaporation rate is about ) prepare 50nm thick gold as the gate, wherein the gate completely covers the channel portion formed between the source and the drain, and the organic transistor memory based on the inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material can be prepared.

[0082] Embodiments 5 to 22

[0083] The differences between the preparation process of the organic transistor memory based on inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material in Examples 5 to 22 and Example 4 are shown in Table 1, and the parts not explained are the same as those in Example 4.

[0084] Table 1 Preparation of organic transistor memory based on inorganic chloride-doped polymer electrolyte hybrid dielectric thin film materials under different embodiments

[0085]

[0086]

[0087] Performance Testing

[0088] 1. Ion migration test characterization of inorganic chloride doped polymer electrolyte hybrid dielectric film materials

[0089] The element distribution test of the zinc chloride doped polymer electrolyte hybrid dielectric film material prepared in the above Example 1 was carried out using a scanning electron microscope (Hitachi SU8010) combined with energy dispersive X-ray spectroscopy (EDS) elemental imaging, and the ion migration phenomenon of zinc chloride doped in the polymer electrolyte dielectric film under different bias voltages was studied. Figure 2 The EDS element distribution diagram of the zinc chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 1 at the initial stage and after voltage application. Figure 2 It can be seen that the elemental mapping of the initial state confirms the uniform distribution of carbon (C), oxygen (O), zinc (Zn) and chlorine (Cl) elements in the polymer electrolyte hybrid dielectric film. After applying a voltage of 10V for 3h, the elemental mapping of the polymer electrolyte hybrid dielectric film shows that the C, O and Cl elements are concentrated near the positive electrode area, indicating that the negatively charged polyacrylate ions and chloride ions migrate toward the positive electrode. At the same time, the Zn element concentration near the negative electrode area indicates that the positively charged zinc ions migrate toward the negative electrode. In addition, after applying a voltage of 20V for 3h, the elemental mapping of the polymer electrolyte hybrid dielectric film shows more significant aggregation behavior of C, O, Zn and Cl elements, indicating that more ions migrate toward their respective electrodes. These results show that applying voltage to the inorganic chloride-doped polymer electrolyte hybrid dielectric film material can effectively promote the migration of charged ions in the film. It can be seen that in this type of inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material, ions rely on applied voltage to achieve adjustable ion migration ability, and the stronger the voltage, the more significant the ion migration effect, so it can be used as the dielectric layer of organic transistor memory to meet storage application needs.

[0090] 2. Capacitance test of inorganic chloride-doped polymer electrolyte hybrid dielectric film materials

[0091] The low frequency (0.1 Hz) capacitance test was performed on the three different inorganic chloride-doped polymer electrolyte hybrid dielectric film materials prepared in Examples 1 to 3 using an LCR digital bridge (TH2827C). The results are summarized in Table 2. It can be seen that the initial state capacitance of the three inorganic chloride-doped polymer electrolyte hybrid dielectric films of zinc chloride, copper chloride and calcium chloride is 150.21, 160.61 and 160.87 nF cm, respectively. -2 After applying -4.5V voltage for 30s, the capacitance of zinc chloride doped film decreased by 29.40nF cm -2 , the copper chloride doping capacitance decreased by 15.10nF cm -2 , the capacitance of calcium chloride doping decreased by 31.69nF cm -2 The results confirmed the mechanism of the effect of ion migration on capacitance in polymer electrolyte dielectric films, indicating that capacitance can be effectively changed by regulating the ion distribution in the film by applying voltage. At the same time, it was also confirmed that copper chloride has the weakest ion migration ability in the film, while calcium chloride has the strongest migration ability.

[0092] Table 2 Comparison of capacitance of hybrid dielectric thin film materials doped with different inorganic chlorides in the initial state and under -4.5V voltage for 30s

[0093]

[0094] 3. Performance testing of organic transistor memory based on inorganic chloride-doped polymer electrolyte hybrid dielectric thin film materials

[0095] The electrical performance of the organic transistor memory prepared in Example 4 was tested using an Agilent 4155c semiconductor parameter analyzer. The transfer and output characteristic curves are shown in FIG. Figure 3 As shown (where a is the transfer characteristic curve and b is the output characteristic curve). Figure 3 It can be seen that the zinc chloride-doped polymer electrolyte hybrid dielectric film material prepared in Example 1 of the present invention and the organic transistor memory prepared accordingly (Example 4) have good transistor characteristics and low voltage working ability. The multi-level writing and erasing behavior test of the organic transistor memory prepared in Example 4 was carried out by combining Agilent 4155c semiconductor parameter analyzer and ultraviolet curing equipment (UVACUBE 100). Figure 4 The multi-level writing characteristics of the organic transistor memory based on the zinc chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 4, wherein the gate pulse voltage action time in a, b and c is 2s, 10s and 30s respectively; Figure 5 The erase characteristics of the organic transistor memory based on zinc chloride-doped polymer electrolyte hybrid dielectric thin film material prepared in Example 4. Figure 4 and Figure 5 It can be seen that the organic transistor memory based on inorganic chloride doped polymer electrolyte hybrid dielectric film material of the present invention has excellent writing and erasing characteristics. In particular, under the same programming gate pulse voltage action time, the larger the gate impulse voltage, the larger the memory window of the organic transistor memory, and the negative pulse voltage causes the memory window of the organic transistor memory to be more significant than the positive pulse voltage; under the same programming gate pulse voltage, the longer the gate impulse voltage action time, the larger the memory window of the organic transistor memory. In addition, after applying programming gate pulse voltages of different amplitudes with the same action time to the organic transistor memory, the threshold voltage of the organic transistor memory will drift to different degrees; similarly, after applying programming gate pulse voltages of different action times with the same voltage amplitude, the threshold voltage of the organic transistor memory will also drift to different degrees; and for each additional level of programming gate voltage voltage amplitude or action time, the threshold voltage will undergo a significant and readable drift change, thereby indicating that the organic transistor memory successfully achieves a controllable threshold voltage change through ion migration in the zinc chloride doped polymer electrolyte hybrid dielectric film, that is, the organic transistor memory has a multi-level storage characteristic. When working at a low voltage of -1.5V, the maximum memory window of the organic transistor memory is 0.548V, that is, 36.5% of the scanning range is converted into a memory window for writing. At the same time, applying a reverse gate pulse voltage can realize the erasing operation of the organic transistor memory, and can achieve rapid erasure by ultraviolet light irradiation (such as Figure 5 shown).

[0096] The electrical pulse response characteristics of the organic transistor memory based on zinc chloride-doped polymer electrolyte hybrid dielectric film prepared in the above Example 4 were tested by using a relay in combination with an Agilent 4155c semiconductor parameter analyzer. By adjusting the programming gate pulse voltage, the electrical pulse response characteristics such as Figure 6 As shown, a is the positive bias electrical pulse response characteristic, and b is the negative bias electrical pulse response characteristic. Figure 6 It can be seen that the pulse current changes with the applied pulse voltage. The higher the pulse voltage, the larger the pulse current and the longer the current duration. When a positive pulse voltage is applied, the organic transistor memory will generate a forward drain current that lasts for more than 14 seconds; when a negative pulse voltage is applied, the organic transistor memory will generate a reverse drain current, and the duration of the current increases with the increase in the amplitude of the applied programming gate pulse voltage. Each increase in the programming gate pulse voltage will result in a significantly increased pulse current gradient change, further indicating that this type of organic transistor memory has multi-level storage characteristics, and further indicating that the organic transistor memory based on inorganic chloride-doped polymer electrolyte hybrid dielectric film in the present invention has excellent dynamic storage characteristics.

[0097] The electrical performance of the other two inorganic chloride-doped polymer electrolyte organic transistor memories prepared in the above-mentioned Examples 5 and 6 was tested using an Agilent 4155c semiconductor parameter analyzer. Their electrical pulse response characteristic curves are shown in FIG. Figure 7 and 8 As shown, a is the positive bias electrical pulse response characteristic, and b is the negative bias electrical pulse response characteristic. Figure 7 and Figure 8 It can be seen that the organic transistor memory of the present invention has a certain sensitivity to different doped inorganic chlorides, can form different amplitudes and variation ranges of electric pulse response currents, and exhibits adjustable storage characteristics.

[0098] Similarly, the performance of the organic transistor memory based on the inorganic chloride-doped polymer electrolyte hybrid dielectric film material prepared in other embodiments was tested according to the above test method, and the results were similar to the performance characteristics of the organic transistor memory based on the zinc chloride-doped polymer electrolyte prepared in the above Example 4, indicating that the organic transistor memory based on the inorganic chloride-doped polymer electrolyte hybrid dielectric film material prepared according to the present invention can also utilize the ion migration characteristics to realize a flexible memory device with low power consumption and multi-level storage characteristics, and has good application prospects in the research of new solid polymer electrolyte hybrid dielectric materials and storage technology in the future.

[0099] In summary, the present invention discloses a polymer electrolyte hybrid dielectric film material based on inorganic chloride doping and its application in organic transistor memory. An electrolyte dielectric film cross-linked with polyacrylic acid and polyethylene glycol doped with zinc chloride is mainly used, and the ion migration in the polymer electrolyte dielectric film is regulated by voltage, and a low-voltage organic transistor memory of an inorganic chloride-doped polymer electrolyte hybrid dielectric film material with multi-level storage characteristics is successfully developed. The organic transistor memory of the inorganic chloride-doped polymer electrolyte of the present invention can give play to the advantages of a three-terminal device, and realize multi-level writing and erasing by applying different programming gate pulse voltages to the gate, and can realize fast storage of the organic transistor memory by ultraviolet light irradiation. At the same time, the organic transistor memory of the inorganic chloride-doped polymer electrolyte can be dynamically stored by electric pulses to meet the needs of fast storage and erasing of information learning and memory type storage devices.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A polymer electrolyte hybrid dielectric thin film material doped with inorganic chloride, characterized in that: The polymer electrolyte hybrid dielectric film material comprises a polymer electrolyte material and a doped inorganic chloride, wherein the mass of the inorganic chloride accounts for 0.05 to 20 wt.% of the total mass of the inorganic chloride and the polymer electrolyte material; The polymer electrolyte material is at least one of acrylamide polymer electrolytes or their derivatives, acrylic acid polymer electrolytes or their derivatives, acrylic acid polymer electrolytes or their derivatives, polymer electrolyte composite dielectric materials formed by blending polyacrylic acid and polyethylene glycol, and polymer electrolyte composite dielectric materials formed by blending polyacrylic acid and polyvinyl alcohol.

2. The inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material according to claim 1, characterized in that: The inorganic chloride is any one or more of zinc chloride, calcium chloride, ferric chloride, copper chloride, cobalt chloride, magnesium chloride, lithium chloride, sodium chloride or potassium chloride.

3. The inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material according to claim 1, characterized in that: The mass ratio of polyacrylic acid to polyethylene glycol in the polymer electrolyte composite dielectric material formed by blending polyacrylic acid and polyethylene glycol is 1:0.1-1:0.6, and the mass ratio of polyacrylic acid to polyvinyl alcohol in the polymer electrolyte composite dielectric material formed by blending polyacrylic acid and polyvinyl alcohol is 1:0.1-1:0.

7.

4. The method for preparing the inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) dissolving a polymer electrolyte in a solvent and stirring at room temperature to obtain a precursor solution of the polymer electrolyte; (2) adding an inorganic chloride to a precursor solution of the polymer electrolyte, and stirring the mixture at room temperature to obtain an inorganic chloride-doped polymer electrolyte solution; (3) After the inorganic chloride-doped polymer electrolyte solution is spin-coated to form a film, the film is annealed at 50-200° C. for more than 30 minutes to obtain an inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material.

5. The preparation method according to claim 4, characterized in that: In step (1), the solvent is any one or more of water, methanol, ethanol or isopropanol, and the concentration of the polymer electrolyte in the polymer electrolyte precursor solution is 3 to 60 mg / mL; In step (2), the stirring time at room temperature is 3 to 24 hours.

6. Use of the inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material according to any one of claims 1 to 3 in the preparation of organic transistor memories, optoelectronic devices or electrical equipment.

7. An organic transistor memory, characterized in that: The organic transistor memory comprises, from bottom to top, a substrate, a semiconductor layer, a double dielectric layer formed by an interface passivation dielectric layer and a polymer electrolyte hybrid dielectric layer, and a gate, and a source electrode and a drain electrode are respectively arranged between the surface of the substrate and the semiconductor layer; The material of the polymer electrolyte hybrid dielectric layer comprises the inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material according to any one of claims 1 to 3.

8. The method for preparing the organic transistor memory according to claim 7, characterized in that: The preparation method comprises the following steps: (1) preparing a source electrode material and a drain electrode material on a substrate surface by any one of magnetron sputtering, vacuum thermal evaporation, atomic layer deposition, inkjet printing or drop coating to form a source electrode and a drain electrode, wherein a conductive channel with a micro-nano scale spacing is formed between the source electrode and the drain electrode; (2) preparing an organic semiconductor material on the surface of the source electrode, the drain electrode and the substrate to form a semiconductor layer by any one of spin coating, blade coating or inkjet printing; (3) on the surface of the semiconductor layer, the material of the interface passivation dielectric layer is prepared by any one of atomic layer deposition, vacuum thermal evaporation, magnetron sputtering, spin coating, blade coating or inkjet printing to form an interface passivation dielectric layer; (4) on the surface of the interface passivation dielectric layer, coating the inorganic chloride-doped polymer electrolyte hybrid dielectric thin film material according to any one of claims 1 to 3 by any one of solution processing methods such as spin coating, blade coating or inkjet printing, and then annealing to prepare an inorganic chloride-doped polymer electrolyte hybrid dielectric layer; (5) On the surface of the inorganic chloride-doped polymer electrolyte hybrid dielectric layer, a gate material is prepared by any one of magnetron sputtering, vacuum thermal evaporation, atomic layer deposition, inkjet printing or drop coating to form a gate, thereby obtaining an organic transistor memory.

9. The preparation method according to claim 8, characterized in that: In step (1), the material of the substrate is any one or more of polyethylene terephthalate, polyethylene naphthalate, polyimide, polydimethylsiloxane, polycarbonate, polyvinyl alcohol, glass, silicon dioxide / silicon or sapphire, and the source and drain materials are any one or more of gold, silver, aluminum, copper, chromium, platinum, titanium, nickel, indium tin oxide, fluorine-doped tin oxide, zinc aluminum oxide, carbon nanotubes, graphene or conductive polymers; In step (2), the material of the semiconductor layer is an organic conjugated polymer or an organic small molecule semiconductor material, and the material of the semiconductor layer includes any one or more of poly (3-hexylthiophene), indacen-dithiophene-benzothiadiazole copolymer, polythiophene derivatives, polyfluorene derivatives, poly(p-phenylene vinylene) derivatives, pentacene, 7,7,8,8-tetracyanoquinodimethane or copper phthalocyanine; In step (3), the material of the interface passivation dielectric layer is any one or more of polymethyl methacrylate, polystyrene, a polymer with a dielectric constant greater than 3, a metal oxide dielectric or silicon dioxide; In step (4), when spin coating is used as the solution processing method, the spin coating speed is 200 to 5000 rpm, the spin coating time is 20 to 150 s, the temperature of the annealing treatment after spin coating is 50 to 200° C., and the annealing time is not less than 30 min; In step (5), the gate material is any one or more of gold, silver, aluminum, copper, chromium, platinum, titanium, nickel, indium tin oxide, fluorine-doped tin oxide, zinc aluminum oxide, carbon nanotubes, graphene or conductive polymers.

10. Use of the organic transistor memory according to claim 7 in static storage, dynamic storage, optoelectronic devices or electrical equipment.

Citation Information

Patent Citations

  • Electric storage device based on one-dimensional organic / inorganic hybrid polymer chain and preparing method thereof

    CN108615813A

  • High-transconductance ionic gel-based all-solid-state organic electrochemical transistor and preparation method thereof

    CN117479551A

  • Preparation method of In-doped ZnO electron transport layer film

    CN117560975A